Innovation bundles and platforms - a qualitative analysis of health system responses to the COVID-19 pandemic - Hania Rahimi-Ardabili; Farah Magrabi; Brenton Sanderson; Thilo Schuler; Enrico Coiera (BMC, 2024)
Abstract Background Health systems underwent substantial changes to respond to COVID-19. Learning from the successes and failures of health system COVID-19 responses may help us understand how future health service responses can be designed to be both effective and sustainable. This study aims to identify the role that innovation played in crafting health service responses during the COVID-19 pandemic. Methods Semi-structured interviews were conducted online, exploring 19 health professionals' experiences in responding to COVID-19 in a large State health system in Australia. The data were collected from April to September 2022 and analysed utilising constant comparative analysis. The degree of innovation in health service responses was assessed by comparing them to pre-pandemic services using 5 categories adopted from the IMPISCO (Investigators, Methods, Population, Intervention, Setting, Comparators and Outcomes) framework, which classifies interventional fidelity as: 1/ Identical: No differences are found between health services; 2/ Substitution with alternatives that perform the same function, 3/ In-class replacement with elements that delivers roughly the same functionality, 4/ Augmentation with new functions, 5/ Creation of new elements. Services were decomposed into bundles and fidelity labels were assigned to individual bundle elements. Results New services were typically created by reconfiguring existing ones rather than being created de novo. The presence of pre-existing infrastructure (foundational technologies) was seen as critical in mounting fast health service responses. Absence of infrastructure was associated with delays and impaired system responses. Conclusions The need to reconfigure rapidly and use infrastructure to support this suggests we reconceive health services as a platform (a general-purpose service upon which other elements can be added for specific functions), where a common core service (such as a primary care practice) can be extended by adding specialised functions using mediators which facilitate the connection (such as virtual service capabilities). Innovation can be costly and time consuming in crises, and during the COVID-19 pandemic, innovations were typically patched together from pre-existing services. The notion of platforms seems a promising way to prepare the health system for future shocks.